Sudden Decline in Semen Volume Due To Seminal Vesicle Fistula in a Patient with Crohn’s Disease: A Case Report - Yumura, Yasushi; Noguchi, Kazumi; Moriyama, Masatoshi; Iwasaki, Akira (Urology Journal, 2014)